Web-Based Academic Assessment System for Elementary Schools - Moch Alex Aliuddin; Munwarah Munawarah (NEWTON: Networking and Information Technology, 2025)
This study describes the creation and development of an online academic evaluation system aimed at handling student test scores in primary schools. The system was designed to solve problems associated with the traditional assessment method, which frequently results in inefficiencies, delays, and risks of losing data. A qualitative research method was used, which involved collecting information through observation, documentation, and the examination of how academic data is managed in educational institutions. The system features easy-to-use interfaces, organized databases, and secure access designed for varying user roles such as teachers and administrators. It allows for the input, processing, and reporting of student scores from midterm and final exams within a comprehensive and centralized system. During the design stage, system analysis, database design, and interface mockups were conducted to ensure the solution meets the specified requirements. Testing was carried out to assess functionality, data precision, and user-friendliness, resulting in a dependable platform for academic record management. This system aims to enhance the efficiency of score administration, diminish calculation and reporting errors, and provide a centralized data storage that is accessible in real-time. The result of this investigation is an operational web-based academic evaluation system that assists schools in improving their data management practices and guarantees that academic records are kept securely and systematically for future reference.